2018
DOI: 10.1002/ajpa.23717
|View full text |Cite
|
Sign up to set email alerts
|

Dental markers of poverty: Biocultural deliberations on oral health of the poor in mid‐nineteenth‐century Ireland

Abstract: ObjectivesDespite subsisting on a low‐cariogenic diet comprising virtually nothing more than potatoes and dairy products, poor oral health affected the quality of life for the poor of nineteenth‐century Ireland. This study investigates potential biocultural reasons that may explain why this was the case.Material and MethodsA total of 6,860 teeth and 9,889 alveoli from 363 permanent dentitions from the skeletal remains of impoverished adult Irish males and females who died between 1847 and 1851 in the Kilkenny … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 86 publications
(55 reference statements)
2
6
0
1
Order By: Relevance
“…However, a previous study comparing oral pathology between Middenbeemster males and earlier pre-tobacco males from Klaaskinderkerke (Figure 1A) identified lower caries rates, and higher AMTL and calculus severity in pipe smoking males in comparison to pre-tobacco males (Inskip et al, n.d.). Similar results were also found by others who had much larger sample sizes with a better representation of pipe users and non–users (Geber and Murphy, 2018; Walker and Henderson, 2010; Western and Bekvalac, 2020). While these results suggest an impact, a confounding issue is that it is not possible to entirely disentangle the influence of smoking versus the abrasion of teeth by clay pipe stems, which may lead to the obliteration of early caries, hence lower caries rates, but also speed up tooth loss due to advanced wear.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, a previous study comparing oral pathology between Middenbeemster males and earlier pre-tobacco males from Klaaskinderkerke (Figure 1A) identified lower caries rates, and higher AMTL and calculus severity in pipe smoking males in comparison to pre-tobacco males (Inskip et al, n.d.). Similar results were also found by others who had much larger sample sizes with a better representation of pipe users and non–users (Geber and Murphy, 2018; Walker and Henderson, 2010; Western and Bekvalac, 2020). While these results suggest an impact, a confounding issue is that it is not possible to entirely disentangle the influence of smoking versus the abrasion of teeth by clay pipe stems, which may lead to the obliteration of early caries, hence lower caries rates, but also speed up tooth loss due to advanced wear.…”
Section: Discussionsupporting
confidence: 88%
“…Pipe notches are areas of dental abrasion caused by habitually clenching a clay pipe between the anterior teeth (Figure 1B, C, Supplemental Figure S1). Multiple studies of these features in 17th-19th century European populations have shown that pipe smoking was a predominantly male activity which varied in popularity over time but increasingly became linked to lower socioeconomic status in the 18th and 19th century (Geber and Murphy, 2018; Inskip et al, n.d.; Kvaal and Derry, 1996; Veselka, 2016; Walker and Henderson, 2010). These trends correspond to historical records about tobacco use and smoking in England and the Netherlands (Goodman, 1993; Hughes, 2003; Tullett, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The average Δ age (16.44 years) was high enough to require thoughtful consideration when choosing an age estimation method and drawing conclusions based on those estimations. Bioarchaeologists often divide skeletal samples into age cohorts of 10–15 years (e.g., Lieverse, Weber, Ivanovich Bazaliiskiy, Ivanova Goriunova, & Aleksandrovich Savel'ev, , Berbesque & Doran, , Rojas‐Sepúlveda, Ardagna, & Dutour, , Šlaus, , Klaus, Larsen, & Tam, , Klaus & Tam, , Scott & Buckley, , Dabbs, , DeWitte & Bekvalac, , Novak & Šlaus, , DeWitte, , Woo & Sciulli, , Da‐Gloria & Larsen, , Griffin, , Marklein, Leahy, & Crews, , Krakowka, , Ostendorf Smith, Kurtenbach, & Vermaat, , Trautmann, Wißing, Díaz‐Zortia Bonilla, Bis‐Worch, & Bocherens, , Geber & Murphy, , Hubbe, Green, Cheverko, & Neves, , Milella, Betz, Knüsel, Larsen, & Dori, , Yaussy & DeWitte, ), and under these conditions, a difference of 16.44 years is enough to move an individual into a different category entirely. There is also considerable variation around the mean Δ age (standard deviation = 11.97), showing that comparing the two methods is not only a matter of correcting them by adding or subtracting a constant.…”
Section: Discussionmentioning
confidence: 99%
“…Geber (2015) undertook skeletal analyses of individuals from the mass burials at the Kilkenny Union Workhouse, poor and starving inmates of the workhouse during the Famine. A general overview on health reveals average stature estimates, enamel hypoplasia, evidence of osteoarthritis and trauma, accidents and violence, as well as a high rate of caries and generally poor dental health, likely due to clay pipe smoking, “one of the comforts the poor could have enjoyed” amidst the “poverty and destitution,” and “the horror of starvation and the mass death” of the Famine (Geber & Murphy, 2018:851). Skeletal pathologies suggested rheumatoid arthritis, tuberculosis, poliomyelitis, and advanced syphilis, an indication that disability might have played a role in workhouse admissions, though vitamin C deficiencies and scurvy were by far the most common pathologies observed in the bone, attesting to the kind of suffering caused by the loss of the potato (Geber, 2015; Geber & Murphy, 2012).…”
Section: The Changing Context For C282y and Iron Metabolismmentioning
confidence: 99%
“…The workhouse was the only state aid supplied under the Irish Poor Law Acts of 1838, the starving and desperate would only receive support in return for their labor. Based on analyses of this collection, Jonny Geber (2014, 2015, 2016) and coworkers (Geber & Murphy, 2012, 2018; Geber & O'Donnabhain, 2020; Geber et al, 2019; additional analyses of the Kilkenny workhouse cemetery include Beaumont & Montgomery, 2016) have begun to build a broad, holistic perspective on the effects of poverty, diet, famine, and workhouse institutionalization on the Irish. Standard markers for life histories and acute and chronic stressors included Harris lines (bone growth arrest lines), whole body growth retardation, and cribra orbitalia, a porosity in orbital bones potentially attributable to iron deficiency.…”
Section: Introductionmentioning
confidence: 99%